Use of Self-Assembling Peptides to Enhance Stem Cell Function for Therapeutic Angiogenesis - Hyung Sub Park; Geum Hee Choi; Daehwan Kim; Tae Woo Jung; In Mok Jung; Jung Kee Chung; Taeseung Lee (Stem Cells International)
The use of nanomaterials for biomedical applications has become a promising field in regenerative medicine. Self-assembling peptides (SAPs) have been proposed as a good candidate because they are able to self-assemble into stable hydrogels and interact with cells or molecules when combined together. This in turn can lead to the improved survival or action of cells or molecules to obtain the desired effects. In this study, we investigated whether the combination of mesenchymal stem cells (MSCs) with SAPs could improve angiogenesis in ischemic hindlimbs of rats compared to MSC or SAP treatment alone. The combination of MSCs and SAPs showed an overall higher expression of angiogenesis markers on fluorescent immunohistochemical analysis and a lower degree of fibrosis and cell apoptosis, which in turn led to an overall tendency for improved perfusion of the ischemic hindlimbs. Finally, SAPs also showed the ability to recruit endogenous host MSCs into the site of action, especially when modified to incorporate substance P as a functional motif, which when injected with exogenous MSCs, allowed for the dual presence of MSCs at the site of action. Overall, these results suggest that SAPs can be applied with stem cells to potentiate angiogenesis, with potential therapeutic application in vascular diseases.